High Temperature Tensile and Strain Hardening Behaviour of AA5052/9 vol. %ZrB2 insitu Composite - Narendra Kumar; Gaurav Gautam; Anita Mohan; Sunil Mohan (Materials Research, 2018)
Various mechanical components such as piston, cylinder blocks, brakes and drums, have to operate under high temperature condition during their service life. Therefore, to meet the demand of high strength materials, a detailed analysis of their synthesis and high temperature tensile behaviour is of utmost importance. Present study is an effort in this direction to develop AA5052/9vol. %ZrB2 insitu composite by salt-metal reaction technique. An insitu reaction between molten aluminium alloy and two inorganic salts K2ZrF6 and KBF4 begins at 860°C and continues up to 30 min. The resulting reaction product ZrB2 is desired reinforcement confirmed by XRD analysis. Microstructural study was performed to analyse grain size, particle morphology, and their distribution in the matrix. Tensile tests were conducted at temperatures ranging from room temperature (RT) to 200°C with an interval of 50ºC. The results revealed the decreasing trend of UTS and YS (0.2% off set) with increase in temperature; however ductility increased with temperature. The composite is able to maintain about 81% of its ambient temperature strength at 150°C and 72% at 200°C. Strain hardening exponent was not significantly affected with temperature and tensile properties were correlated with fractured surface morphology examined under SEM to understand the mechanism.